MICRONEEDLING VERSUS ADAPALENE GEL IN THE MANAGEMENT OF FACIAL PLANE WARTS: A HEAD-TO-HEAD CLINICAL TRIAL - Khan, Jahangir; Gul, Huma; Irfan Ullah,; Mehran Khan,; Muhammad Adnan Rashid, (Journal of Ayub Medical College Abbottabad, 2025)
Background: Development of Plane warts (verruca plana) on face is not uncommon and warrants treatment due to its unsightly appearance. A number of treatment options have been explored till date exhibiting variable efficacy. Adapalene gel is a 3rd generation retinoid that upon application onto the surface of skin can result in clearance of warts. Microneedling, a procedure in which skin is pricked with needles via a device recently gain popularity as it is utilized for a number of dermatological procedures including acne scars, alopecia, vitiligo and for skin rejuvenation. It is hypothesized that the resultant injury induces immune response that can result in clearance of warts. Lack of head-to-head clinical trials comparing the efficacy of microneedling and topical adapalene Gel for treatment of cutaneous warts compelled us to design this clinical research. Objective was to compare the efficacy of microneedling versus Adapalene gel in treatment of facial plane warts. Methods: The research commenced with the assent from hospitals ethical review committee. Clinical diagnosis of plane warts was done and then the study participants were recruited. This clinical trial was managed at Khyber Teaching Hospital, Peshawar from January 2022 to December, 2022. Block randomization was utilized to allocate 100 study participants, equally into group A and group B. Patients gave a written consent and were warned about the possible adverse events. Microneedling was performed on the participants in group A while the other group was advised to apply topical adapalene gel daily onto the surface of warts at night. A total of three microneedling sessions were done i.e. one session every four weeks. Clinical assessment was done monthly and the final evaluation was done after 4 months of initiating of treatment. The intervention was considered successful if all the warts resolved completely. Monthly follow up for a total of 6 months was done to document the recurrences. Results: Twenty-nine (58%) study subjects from group A had complete resolution of lesions. In group B, 22 (44%) participants exhibited complete remission. p=0.1614. Partial response was appreciated in 7 (14%) participants that were treated with Microneedling procedure and 8 (16%) patients from adapalene treated group showed partial improvement. Conclusion: Both Topical adapalene and microneedling are effective in treating facial plane warts.